A microfluidic impedance-based extended infectivity assay: combining retroviral amplification and cytopathic effect monitoring on a single lab-on-a-chip platform. Issue 7 (10th February 2021) - Purtscher, Michaela; Rothbauer, Mario; Kratz, Sebastian Rudi Adam; Bailey, Andrew; Lieberzeit, Peter; Ertl, Peter
Abstract : We have established a lab-on-a-chip for detection, quantification and monitoring of virus – host cell interactions that are of great importance when evaluating the safety of pharmaceutical products. Abstract : Detection, quantification and monitoring of virus – host cell interactions are of great importance when evaluating the safety of pharmaceutical products. With the wide usage of viral based vector systems in combination with mammalian cell lines for the production of biopharmaceuticals, the presence of replication competent viral particles needs to be avoided and potential hazards carefully assessed. Consequently, regulatory agencies recommend viral clearance studies using plaque assays or TCID50 assays to evaluate the efficiency of the production process in removing viruses. While plaque assays provide reliable information on the presence of viral contaminations, they are still tedious to perform and can take up to two weeks to finish. To overcome some of these limitations, we have automated, miniaturized and integrated the dual cell culture bioassay into a common lab-on-a-chip platform containing embedded electrical sensor arrays to enrich and detect infectious viruses. Results of our microfluidic single step assay show that a significant reduction in assay time down to 3 to 4 days can be achieved using simultaneous cell-based viral amplification, release and detection of cytopathic effects in a target cell line. We further demonstrate the enhancing effect of continuous fluid flow on infection of PG-4 reporter cells by newly formed and highly active virions by M. dunni cells, thus pointing to the importance of physical relevant viral–cell interactions.